PENERAPAN SISTEM KEAMANAN DENGAN KRIPTOGRAFI ADVANCED ENCRYPTION STANDARD (AES) DAN KEY ADMINISTRATOR PADA SINKRONISASI FILE - Wawan Qurniawan; Hero Wintolo; Dwi Nugraheny (Compiler, 2012)
File synchronization is the process of homogenization or adjustment between one file at a location with other files in the event that a change to be used up and running in a system. File synchronization is generally a process of data exchange in order to have the same amount of data. To maintain the confidentiality of the data necessary to maintain services for data security.            The use of cryptographic AES (Advanced Encryption Standard) to encrypt the file and combined with the administrator as an authentication key in making additions or changes to the file is a security system that can be applied to synchronize the files so that data confidentiality will be maintained.            The results of the implementation of file synchronization application by applying the AES cryptography and key administrators who carried on the local network and the Internet as a service application data synchronization between the user and the service back-up data as manual handling if storage was damaged and can avoid the theft of data from a file synchronized.